Beyond the jab: Unravelling the complexities of vaccine adoption for East Coast Fever in rural Kenya. - Ann W Muthiru; Josphat Muema; Nyamai Mutono; S M Thumbi; Salome A Bukachi (PLoS ONE)
East Coast Fever (ECF) is one of the leading causes of livestock mortality and reduced productivity across Eastern Africa, and while a live vaccine against it known as the Infection and Treatment Method has existed for three decades now, its adoption by affected communities remains low. This study sought to provide a detailed examination of the dynamics that shape Infection Treatment Method (ITM) vaccine adoption behaviours. The study examined individual, socio-cultural and ecological- level factors influencing ITM adoption using the socio-ecological model. Analyzing data obtained from 18 focus group discussions, 30 in-depth interviews with livestock keepers, and 25 key informant interviews conducted with community stakeholders, the study identified factors associated with vaccine adoption within pastoralist communities in rural Kenya. These factors included knowledge and awareness of the Infection Treatment Method vaccine, its cost, livestock keepers' perceptions of East Coast fever relative to other livestock diseases, wildlife-livestock interactions, climate as contributing factors, and wildlife-livestock interactions influencing ECF risk and severity. Overall, the study findings emphasize the need for multifaceted strategies to increase vaccine adoption among livestock keepers.